The Relationship between Audit Committee Compositions and Audit Fees of Listed Companies in The Stock Exchange of Thailand - เยาวมาร ปริศนา; ชัยเขต เนตรดาว; รอดหริ่ง กมลวรรณ (KKBS Journal of Business Administration and Accountancy, 2018)
This study aimed at identifying information about audit committee composition and qualifications of audit committee, as well as the relationship between audit committee composition and audit fees of listed companies in The Stock Exchange of Thailand. The audit committee composition consists of (1) a number of audit committee members, (2) independence of audit committee members, (3) knowledge and expertise in accounting or finance of audit committee members, and(4) anumber of audit committee attendance. The samples includeThai listed companiesbetween 2012 and 2016, total 442 companies. Descriptive statistics (mean, minimum, maximum, and standard deviation) and inferential statistics (multiple regression analysis technique) were used to describe the results and test the relationship between audit committee composition and audit fees. As expected at 95% confidence interval,independent of audit committee members, knowledge and expertise in accounting or finance of audit committee members, and a number of audit committee attendance positively associated with the audit fees, while a number of audit committee members negatively associated with the audit fees. Furthermore, the study also found that company size, company complexity, operating loss, and type of audit firm positively associated with the audit fees.